The Association Between Cigarette Smoke Exposure and Hypertension Incidence in Managaisaki Public Health Center, Tolitoli District - Sova Evie; Hasni Hasni; Novica Ariyanti Putri; Alfrida Semuel Ra'bung; Rahmat Kurniawan; Saman Saman; Dwi Yogyo Suswinarto; Azwar Azwar; Enggar Enggar (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
Smoking remains a major global public health concern and is strongly associated with cardiovascular diseases. This study aimed to analyze the relationship between cigarette smoke exposure and hypertension incidence among residents in the working area of Managaisaki Public Health Center, Tolitoli District. This observational analytic study employed a cross-sectional design with 40 respondents. Independent variables included duration of exposure, type of cigarette, and carbon monoxide (CO) levels in the body, while hypertension incidence was the dependent variable. Data were analyzed using chi-square test, with p<0.05 considered statistically significant. The results showed that 60% of respondents had high smoke exposure, 55% were exposed to unfiltered cigarettes, and 45% had hypertension. Bivariate analysis revealed no significant relationship between duration of exposure (p=0.080) and type of cigarette (p=0.307) with hypertension. However, CO levels were significantly associated with hypertension (p=0.006), where respondents with high CO exposure were more likely to have hypertension. In conclusion, cigarette smoke exposure, particularly elevated CO levels, increases the risk of hypertension. These findings emphasize the importance of tobacco control measures and monitoring CO exposure as a preventive strategy against hypertension.